Islamic babble: portrayal of religious arabic phrases in english rhythm and blues (R&B) and hip-hop lyrics - Kartika, Dilah Ratna; Muhammad Rizki Alpasya; Prudence Ardhaneswary Purnomo (The Journal of Religion and Communication Studies, 2024)
Background: The spread of rhythm and blues (R&B) and hip-hop songs among youth is undeniable nowadays. Besides the alluring arrangement of musical sounds those genres offer, people also appreciate the meaning of the lyrics. However, some musicians would slip religious Arabic phrases into their lyrics regardless of the song's overall content, evoking questions regarding their appropriateness. This research aims to raise awareness among Muslim youth about the implied message behind R&B and hip-hop songs, as well as to track the development of Islamic teachings regarding music. Methods: Mixed-method approach, consisting of questionnaires and follow-up interviews with respondents, was adopted in the data collection process. The data includes the opinions of 30 participants regarding the phenomenon of religious Arabic phrases in the lyrics of English R&B and hip-hop songs. Findings: This research has found five English hip-hop and R&B songs that contain religious Arabic phrases. A majority of the participants have heard of English hip-hop and R&B songs with religious Arabic phrases, and most of them understand the meaning behind the song lyrics. Conclusion: This research concludes that when employing religious Arabic phrases in English hip-hop and R&B, it is regarded as inappropriate and strictly prohibited if the phrases are utilized in a hypocritical context or to make light of religion. Novelty/Originality of This Study: This study raises awareness among Muslim youth about the implied messages behind R&B and hip-hop songs with religious Arabic phrases and tracks the development of Islamic teachings regarding music, addressing an area that combines contemporary music trends with religious sensitivity.